Investigating the impacts of COVID-19 on aviation safety based on occurrences captured through flight data monitoring - Li, Wen-Chin; Nichanian, Arthur; Lin, John; Braithwaite, Graham (Taylor & Francis, 2022)
The COVID-19 pandemic led to growing concerns about pilots’ proficiency due to the significant decrease in flight operations. The objective of this research is to provide a proactive approach to mitigate potential risks in flight operations associated with the impact of the COVID-19 pandemic using flight data monitoring (FDM). The results demonstrated significant associations between the pandemic impacts and FDM exceedance categories, flight phases and fleets. Manual flying skill decay, lack of practice effects on use of standard operating procedures and knowledge of flight deck automation should be considered by airlines when preparing for the return to normal operations. An FDM Programme allows prediction of the probability and severity of occurrences for developing an effective SMS within an airline. To mitigate the impacts of the pandemic, tailored training sessions must be implemented, and airlines should strive to avoid additional optional procedures where practicable.
Keywords: Aviation safety; COVID-19; flight data monitoring; operational proficiency; safety resilience